Characterization of Enterococcus Faecalis Isolates Originating From Different Sources for Their Virulence Factors and Genes, Antibiotic Resistance Patterns, Genotypes and Biofilm Production - Gülhan, T.; Boynukara, B.; Çiftçi, A.; Söğüt, M.U.; Findik, A. (Shiraz University PO Box 1731 Shiraz 71345, 2015)
In this study, 72 Enterococcus faecalis isolates originating from humans (n=39), dogs (n=26) and cats (n=7) were investigated for some virulence factors, some virulence genes, antibiotic resistance phenotypes, randomly amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) patterns and biofilm production. Of the isolates, 31 (43.1%) were positive for gelatinase, 11 (15.3%) for aggregation substance and cytolysine, 38 (52.8%) for gelE and 34 (47.2%) for asa1 genes. All isolates were found to be negative for hyl, esp and cylA genes. All isolates were found to be resistant to nalidixic acid and kanamycin. On the other hand, all isolates were cited for susceptible to amoxicillin. Vancomycin resistance genes (vanA, vanB, vanC1/C2 or vanD) have not been detected in any of the phenotypically vancomycin resistant isolates. Isolates from humans, dogs and cats were grouped into 8, 2 and 4 antibiotypes depending upon susceptibilities to 12 different antibiotics. In all human, dog and cat isolates, 9, 12 and 2 genotypes were determined by RAPD-PCR, respectively. Nine (34.6%) of the dog isolates were found to be positive for biofilm production. This study showed that multiple antibiotic resistance among human isolates is more frequent than in dog and cat isolates.
Keywords: Antibiotyping; Biofilm; Enterococcus Faecalis; Genotyping; Virulence